Exploring perspectives on changing opioid prescribing practices: A qualitative study of community stakeholders in the HEALing Communities Study. (1st April 2022) - Walker, Daniel M.; Childerhose, Janet E.; Chen, Sadie; Coovert, Nicolette; Jackson, Rebecca D.; Kurien, Natasha; McAlearney, Ann Scheck; Volney, Jaclyn; Alford, Daniel P.; Bosak, Julie; Oyler, Douglas R.; Stinson, Laura K.; et al.
Abstract: Background: Community-based perspectives are needed to more broadly inform policy-makers, public health practitioners, prescribers, and pharmacists about community-led and broader efforts to reduce opioid overprescribing, and ultimately reduce prescription opioid use disorder, overdoses and fatalities. The aim of this study is to explore community-based perspectives on efforts to change opioid prescribing practices in their communities. Methods: Semi-structured interviews were conducted with 388 community stakeholders across four states (Kentucky, Massachusetts, New York, Ohio) from November 2019 to January 2020 about community approaches and goals of community-led responses to the opioid crisis. Data analysis combined deductive and inductive approaches to identify themes and sub-themes related to improving opioid prescribing practices. Results: Three major themes and different subthemes were characterized: (1) acknowledging progress (i.e., healthcare providers being part of the solution, provider education, and prescription drug monitoring programs); (2) emergent challenges (i.e., physician nonadherence with safer opioid prescribing guidelines, difficulty identifying appropriate use of opioids, and concerns about accelerating the progression from opioid misuse to drug abuse); and (3) opportunities for change (i.e., educating patients about safer use and proper disposal of opioids, expanding prescriber and pharmacist education, changing unrealistic expectations around eliminating pain, expanding and increasing insurance coverage for alternative treatment options). Conclusions: Community stakeholders appeared to support specific opportunities to reduce prescription opioid misuse and improve safer prescribing. The opportunities included culture change around pain expectations, awareness of safe disposal, additional provider education, and increased coverage and acceptability of non-opioid treatments. Highlights: Community stakeholders acknowledge progress in changing opioid prescribing. Emergent challenges impede efforts to improve safer opioid prescribing. Community stakeholder identified several opportunities for further change.